How long can you hold the filler: maintenance and retrieval. Issue 1 (2nd January 2020) - Kim, Nayoun; Brehm, Laurel; Sturt, Patrick; Yoshida, Masaya
ABSTRACT: This study attempts to reveal the mechanisms behind the online formation of Wh-Filler-Gap Dependencies (WhFGD). Specifically, we aim to uncover the way in which maintenance and retrieval work in WhFGD processing, by paying special attention to the information that is retrieved when the gap is recognized. We use the agreement attraction phenomenon (Wagers, M. W., Lau, E. F., & Phillips, C. (2009). Agreement attraction in comprehension: Representations and processes. Journal of Memory and Language, 61 (2), 206–237) as a probe. The first and second experiments examined the type of information that is maintained and how maintenance is motivated, investigating the retrieved information at the gap for reactivated fillers and definite NPs. The third experiment examined the role of the retrieval, comparing reactivated and active fillers. We contend that the information being accessed reflects the extent to which the filler is maintained, where the reader is able to access fine-grained information including category information as well as a representation of both the head and the modifier at the verb.